Kids are consumers, too! real-world mathematics for today's classroom - Fair, Jan; Melvin, Mary (Reading, MA Addison-Wesley Publishing Company, 1986)
Help students get a grasp on consumerism with more than 100 activities and projects on estimating grocery weights, comparing salaries in different parts of the U.S., writing invoices, and more. As students explore these real-life situations, they learn to use decimals, charts and tables, estimation, fractions, geometry, measurement, and graphing. Blackline masters and teaching tips are included.
Includes blackline masters with publisher's permission to reproduce.
Keywords: Mathematics -- Study and teaching; Consumer education; Problem solving -- Study and teaching; Youth as consumers